Cannabis legalization with strict regulation, the overall superior policy option for public health. Issue 6 (2nd May 2015) - Rehm, J; Fischer, B
<x xml:space="preserve">Abstract</x> Cannabis is the most prevalently used drug globally, with many jurisdictions considering varying reform options to current policies to deal with this substance and associated harm. Three policy options are available: prohibition, decriminalization, and legalization, with prohibition currently the dominant model globally.1 This contribution gives reasons why legalization with strict regulation should be considered superior to other options with respect to public health in high income countries in North America.